ORGANIC CARBON IN THE SEDIMENTS OF THE LOWER REACHES OF PERIAR RIVER - SARALADEVI, K.; VENUGOPAL, P.; SANKARANARAYANAN, V. N. (Journal of Indian Fisheries Association, 2015)
Sediments are indicators of the quality of water overlying them and hence, useful in the assessment of environmental pollution. Temporal and spatial variations in sediment characteristics and organic carbon content from 9 stations in the lower reaches of Periyar river an area in Cochin Backwater which is polluted from different sourcesÂ· were studied for one year during 1981. Variations in colour and texture of sediments were brought about by changes in the grain size and state of oxidation of organic matter. The colour of the sediment varied from greyish black at stations 1 and 2, brownish at station 3, black at stations 4 to 8 and reddish at station 9. Organic carbon and sediment texture showed a direct relationship at all stations except at station 9 where organic carbon content showed an irregular pattern. Overall range of organic carbon content was between 1.19 and 29.6 mg.g-1â€¢ The mean organic carbon of the stations ranged between 6.8 mg.g-1 (station 5) and 20.8 mg.g-1 (station 9). On the whole temporal variations were considerable with high values at station 9 and low values at station 5. Fluctuations were more at stations 6,7 and 8.